Modelagem cinética da produção de propeno a partir de acetona em uma única etapa - Enzweiler, Heveline (2014)
Propylene is a chemical compound with high value added, widely used in the industry and usually obtained from petroleum. However, there is the need of the development of alternative routes for the production of this compound from renewable sources. The use of acetone for the production of propylene is a good option, because this oxygenated compound can be obtained by biomass conversion. The use of a one step process also adds an advantage to the propylene production from acetone, uniting in a single reactor two consecutive reactions: acetone hydrogenation, followed by dehydration of the formed isopropanol. For this, there are necessary two catalysts with distinct properties, one containing metallic sites, for hydrogenation, and another where there are acidic sites, for dehydration. The main objective of this work is to obtain propylene from acetone in one single step, using Cu/Zn/Al mixed oxide derived from hydrotalcite-like compounds and acid form of Beta zeolite as catalysts. For that, the catalysts were obtained by the coprecipitation method at variable pH followed by calcination, for the mixed oxide, and by hydrothermal synthesis, for the zeolite. The catalysts were also characterized as their with distinct properties. The hydrogenation and dehydration reactions have been studied individually and together by varying the catalyst or mixture of catalysts employed and the composition and flow rate of the feed. First, they were evaluated the thermodynamic boundaries of the reaction systems in which was observed that the acetone hydrogenation is strongly limited by the equilibrium and which are the preferential products of each reaction. For the reaction test, it was used the factorial experimental design, where the feeding conditions and reaction temperature were varied, and as response variables it was obtained the composition of the organic fraction at the reactor outlet. In the hydrogenation reaction, only isopropanol was obtained and the acetone conversion was close to that of equilibrium. In the dehydration reaction of isopropanol, propylene was preferably formed, with only small concentrations of diisopropyl ether at low temperatures, being obtained complete alcohol conversion in some experimental conditions. The complete process of acetone conversion into propylene was carried out at eleven distinct experimental conditions and the olefin fraction was up to 65 % of the organic fraction. It was possible the parameters estimation of simplified kinetic models, considering the Langmuir-Hinshelwood hypothesis, appropriate to the prediction of the molar fractions of the compounds in the organic fraction for both individual as simultaneous reactions. The kinetic models were used to the analysis of the effect of process variables on the reaction products in the three reaction systems considered.